Conceptuality x reality, the current conjuncture for the implementation of industry 4.0 in Brazil - Silva, Vinícius Radetzke da; Santos, Alicy Ferreira Lopes dos; Limana, Ermilo Sampaio; Tambara, Vityano Buzata; Silva, Ana Carolina Cozza Josende da (Revista de Administração da UFSM, 2020)
Purpose: To analyze the impact of technological evolution on industrial production capacity and how Industry 4.0 can be developed for the Brazilian industrial scenario. Design/methodology/approach:Data collection was through the selection of studies - scientific articles, books, dissertation, among others - current and relevant on the topic, through an exploratory descriptive research, as well as the use of an electronic platform such as Google Scholar, Journals CAPES, Scielo and Scopus. The analysis took place through reading, comparison and discussion between the different authors and studies found. Findings: The results evidenced, show that the Brazilian context falls short of what would make the country a player of world production. The roles in this process process an integrating responsibility between governments, companies and international partnerships, for a more agile adaptation to the latest world production model. Practical Implications: Investments by political-governmental segments are still ineffective, compromising the generation of wealth, taxes and fees in Brazilian companies. Social Implications: Thematic contemporary to the reality of the country, in order to offer new alternatives for research and knowledge to be used by companies, academics and society. Originality/Value: It consists of investigating the current level of industry 4.0 dimensions in the Brazilian context, and proportional improvement for national companies in global markets.